Interplay Between ncRNAs and Cellular Communication: A Proposal for Understanding Cell-Specific Signaling Pathways - Ramón y Cajal, Santiago; Segura, Miguel F.; Hümmer, Stefan (Frontiers in Genetics, 2019)
Intercellular communication is essential for the development of specialized cells, tissues and organs and is critical in a variety of diseases including cancer. Current knowledge states that different cell types communicate by ligand-receptor interactions: hormones, growth factors, and cytokines are released into the extracellular space and act on receptors, which are often expressed in a cell-type-specific manner. Noncoding RNAs (ncRNAs) are emerging as newly-identified communicating factors in both physiological and pathological states. This class of RNA encompasses microRNAs (miRNAs, well-studied post-transcriptional regulators of gene expression), long noncoding RNAs (lncRNAs) and other ncRNAs. Long noncoding RNAs are diverse in length, sequence and structure (linear or circular), and their functions are described as transcriptional regulation, induction of epigenetic changes and even direct regulation of protein activity. They have also been reported to act as miRNA sponges, interacting with miRNA and modulating its availability to endogenous mRNA targets. Importantly, lncRNAs may have a cell-type-specific expression pattern. In this paper, we propose that lncRNA-miRNA interactions, analogous to receptor-ligand interactions, are responsible for cell-type-specific outcomes. Specific binding of miRNAs to lncRNAs may drive cell-type-specific signaling cascades and modulate biochemical feedback loops that ultimately determine cell identity and response to stress factors.